Pengaruh Budaya Organisasi, Pelatihan, dan Pengembangan Karir terhadap Prestasi Kerja Karyawan di PT. Kurabo Manunggal Textile (KUMATEX) - Maudyna, Adila Balqsi; Murniadi, Murniadi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine the effect of Organizational Culture, Training, and Career Development on Employee Performance at PT. Kurabo Manunggal Textile (KUMATEX). This study uses a quantitative approach, with a research sample of 107 respondents. The results of this study show that, partially, the Organizational Culture variable (X1) has a significant effect on Employee Performance (Y) with a tcount of 2.972 > ttable 1.983, Training (X2) has a significant effect on Employee Performance (Y) with a tcount of 2.847 > ttable 1.983, Career Development (X3) has a significant effect on Employee Performance (Y) with a tcount of 12.678 > ttable 1.983. The results of the study show that, simultaneously, Organizational Culture (X1), Training (X2), and Career Development (X3) have a significant effect on Employee Performance (Y) with an Fcount of 84.506 > Ftable 2.69. With the multiple regression equation value Y = 21.254 + 0.054 + 0.047 + 0.177 and a coefficient of determination of 71.1%, the remainder is influenced by other factors not studied.   Keywords: Organizational Culture, Training, Career Development, Employee  Performance